FYR Macedonia Public Expenditure Review : Fiscal Policy for Growth - World Bank Group (World Bank, Washington, DC, 2016)
FYR Macedonia is a small, open economy with solid economic growth. It reached independence in 1991. Though it was the first among the six countries in South East Europe (SEE6) 7 to gain EU candidate status in 2005, it has not been able to start negotiations for EU accession, partly because of its name dispute with Greece. Yet, EU accession is the main anchor of its reform agenda and all major political parties and over 80 percent of the people support EU membership. Landlocked, with a population of 2.1 million, the country GDP per capita is USD 5371. FYR Macedonia has enjoyed macroeconomic and financial stability during the last decade. Growth has been solid with an annual real GDP per capita growth in PPP terms of 3.7 percent between 2006 and 2014. This was the second highest growth rate among the countries of South East Europe and far above the EU28 average of 1.4 percent during this period, enabling FYR Macedonia to increase its per capita income relative to the EU28 from 30.7 percent in 2006 to 36.6 percent in 2014. Contrary to other SEE6 countries, unemployment in FYR Macedonia has declined since the 2009, yet gains in poverty reduction seem to have been moderate. Fiscal stimulus was largely driven by revenue-reducing measures and public investment. Between 2006 and 2013, general government spending averaged about 34.5 percent of GDP, which is significantly below the SEE6 and the Europe and Central Asia (ECA) average. At the same time, general government revenues declined steeply from 33.8 percent of GDP in 2007 to 27.8 percent in 2014, one of the lowest in the ECA region as the government reduced its rates on the corporate income tax and personal income tax as well as social security contributions. Also, debt financed investments of SOEs increased. As a consequence, public debt increased, undoing the gains of previous fiscal consolidation but enabling FYR Macedonia to sustain growth in times of a difficult external environment.